2017
DOI: 10.1007/s00467-017-3841-y
|View full text |Cite
|
Sign up to set email alerts
|

Iohexol plasma clearance in children: validation of multiple formulas and single-point sampling times

Abstract: BackgroundThe non-ionic agent iohexol is increasingly used as the marker of choice for glomerular filtration rate (GFR) measurement. Estimates of GFR in children have low accuracy and limiting the number of blood-draws in this patient population is especially relevant. We have performed a study to evaluate different formulas for calculating measured GFR based on plasma iohexol clearance with blood sampling at only one time point (GFR1p) and to determine the optimal sampling time point.MethodsNinety-six childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The latter was confirmed in children by Tøndel et al . (single: >30 mL/min/1.73 m²; double: <30 mL/min/1.73 m²) 26 . In future studies, the use of single- or double-plasma sampling approaches could be evaluated in avian species as well, whereby a mathematical correction for the first fast exponential curve based on the slope-intercept method proposed by Brochner-Mortensen could be incorporated 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The latter was confirmed in children by Tøndel et al . (single: >30 mL/min/1.73 m²; double: <30 mL/min/1.73 m²) 26 . In future studies, the use of single- or double-plasma sampling approaches could be evaluated in avian species as well, whereby a mathematical correction for the first fast exponential curve based on the slope-intercept method proposed by Brochner-Mortensen could be incorporated 27 .…”
Section: Discussionmentioning
confidence: 99%
“…CKD cohort: children and adolescents < 18 years of age with CKD were included in a cross-sectional study, evaluating biomarkers in CKD and different methods of measuring glomerular filtration rate (mGFR). The children were in a stable phase of their CKD and enrolled at the pediatric departments at Oslo University Hospital and Haukeland University Hospital [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…at 10 and 20 min, or even only one at 15 min) in the early (distribution) phase may (partially) solve this, but this requires additional discomfort for the patient. Moreover, studies with earlier time-points have reported the same fitting problems [ 24 ].…”
Section: Discussionmentioning
confidence: 81%
“…Only a few iohexol studies have been published including early (< 120 min) and late time-points [ 5 , 16 , 23 , 24 ] and the ‘accuracy’ of the obtained GFR from the double-exponential decay curve has not been questioned so far. In the current study we have shown that the fitting procedure has significant influence on the obtained coefficients for the double exponential decay curve.…”
Section: Discussionmentioning
confidence: 99%